SOP for the determination and quantification of phenolic compounds in bean flour by HPLC - Orozco Agredo, Juan Camilo; Londoño Hernandez, Luis Fernando; Taleon, Victor; Gallego Castillo, Sonia (2025)
This SOP describes the stages of the extraction process, drying, identification, and quantification of the main phenolic compounds in common beans (Phaseolus vulgaris L.) using high-performance liquid chromatography (HPLC)